Someone like Me: Descriptive Representation and Support for Supreme Court Nominees. (March 2018) - Badas, Alex; Stauffer, Katelyn E.
Extant research on public support for judicial nominees finds that ideological congruence with the nominee is the most important factor in an individual's decision to support a nominee. The research presented in this article develops the theory that for individuals from underrepresented groups, a shared descriptive identity with the nominee will moderate the negative effect of ideological distance. We test our theory using the nominations of Clarence Thomas, Elena Kagan, and Sonia Sotomayor. Furthermore, we conduct placebo tests to determine whether the effect of ideology is moderated for underrepresented groups when a shared descriptive identity is not present. We find that in the context of the Thomas nomination, a shared racial identity led to increased support for Thomas among liberal African Americans. We find similar effects in the case of Kagan and conservative women. In the case of Sotomayor, we find that a shared ethnic identity led to increased support among conservative Latinos, regardless of gender. We conclude by discussing the implications our findings have for descriptive representation and presidential selection of judicial nominees.